SANDS of SAHARA: Post-laser in situ keratomileusis late-onset diffuse lamellar keratitis following sports injury - Nidhi Sharma; Rajender Singh Chauhan (Asian Journal of Medical Sciences, 2025)
A 27-year-old male presented with decreased vision and pain in his left eye after a boxing injury, 1 year post-LASIK. Examination showed a partially dislocated LASIK flap, leading to diffuse lamellar keratitis (DLK). Surgical realignment and treatment with topical steroids restored his visual acuity to 20/20 within 3 weeks. This case emphasizes the need for prompt intervention and long-term post-operative care for managing late-onset DLK following high-velocity blunt ocular trauma.